Ventricular transmural decremental conduction explains short t-peak-t-end interval in "in silico" ECG reconstruction model. (25th November 2020) - Benchimol Barbosa, P.R; Barbosa, E.C; Barbosa, E.C
Abstract: Introduction: In chronic hepatic cirrhosis (CHC), T-wave peak to T-wave end interval (TPTE) has shown prognostic value for survival and liver transplantation. Altered cellular ionic regulatory systems may produce decremental conduction in ventricular endocardial to epicardial activation wavefront propagation and ECG waveforms, particularly the T-wave. It was investigated whether ventricular transmural activation wavefront conduction may affect T-wave shape and impact TPTE duration, using "in silico" ECG reconstruction. Methods: Mammalian-derived ventricular endocardial to epicardial AP waveforms (APW) were simulated and deployed in 10 discrete layers in homogeneous impedance ventricular wedge-like model. A uniform conduction model was employed to mimic normal heart, in which the speed of propagation of the activation wavefront was nonzero and constant in all layers. In CHC heart, a decremental conduction model was employed, in which the speed of propagation of the activation wavefront was maximal at the endocardial layer and exponentially decayed to greater than zero speed at the epicardial layer. ECG was computed as the sum of dipoles weighted by the inverse of the squared distance to an observation electrode arbitrarily located outside the wedge. One dipole was one layer thick, and its charge was assumed as the time-integral of the current generated by the difference of potential between adjacent APW, from endocardial to epicardial layers. ECG was reconstructed in one axis. Results: Two-dimensional transmural APW distribution and respective reconstructed ECGs are presented in Figures 1 and 2. In uniform endocardial to epicardial transmural conduction model, QRS complex was taller and shorter as well as TPTE was larger (Fig. 1) than respective counterparts in decremental conduction model (Fig. 2). Additionally, peak-amplitude of the T-wave as well as the maximal slope of the TPTE were lower in decremental as compared to uniform conduction model. Conclusion: Using "in silico" ECG reconstruction, decrementally conducted model of epicardial to endocardial ventricular transmural activation wavefront propagation yields wider and lower amplitude QRS complex as well as shorter TPTE, as compared to respective counterparts in uniformly conducted activation wavefront model. Ventricular transmural decremental conduction model offers an insight into electrophysiological background of ECG findings in CHC. (NCT01433848) Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Universidade do Estado do Rio de Janeiro; Rio de Janeiro, RJ - Brazil